ASUHAN KEPERAWATAN KELUARGA PADA KLIEN DENGAN ARTHRITIS GOUT DENGAN TERAPI PEMBERIAN KOMPRES HANGTA MENGGUNAKAN LARUTAN JAHE DI TJ. PENGAPIT TAHUN 2024 - Stela Afrisa Fajar; Isna Aglusi Badri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Family nursing is a comprehensive service that places the family and its parts at the focus of service and involves family members in assessment, nursing diagnosis, planning, implementation and evaluation. According to the Ministry of Health of the Republic of Indonesia (Kemenkes RI, 2020). Gouty arthritis or also known as gout is a disease that attacks the joints. This is due to increased uric acid levels due to genetic factors and lifestyle factors, such as frequent consumption of foods rich in purine. Purines are an important part of protein, and most of the protein is obtained from organ meats, meat, nuts, etc. (Megayanti, 2022). This case study aims to provide nursing care for Mrs. R by treating pain using complementary therapy, namely warm compresses using ginger solution on Tj. Pengapit Year 2024. The method used in this scientific work is a case study. The results of the assessment obtained by the researcher came to the patient's house with the client's leg feeling pain in the right knee area since 4 days ago with a nursing diagnosis of acute pain. The intervention and implementation provided was in the form of warm compress therapy using ginger solution for 5 consecutive days. The results of nursing care for Mrs. R with Gouty Arthritis who experienced joint pain in the knee area on the right leg and after implementing nursing for 5 consecutive days, the pain in the knee on the right leg decreased, and the difficulty in moving decreased. Application of non-pharmacological therapy with warm compresses using this ginger solution in patients who experience pain in gouty arthritis.Keywords: Nursing Care, Gouty Arthritis, Joint Pain, Complementary Therapies